Of thee I sing : a letter to my daughters - Obama, Barack (Alfred A. Knopf, 2010)
"In this tender, beautiful letter to his daughters, President Barack Obama has written a moving tribute to thirteen groundbreaking Americans and the ideals that have shaped our nation. From the artistry of Georgia O'Keeffe, to the courage of Jackie Robinson, to the patriotism of George Washington, President Obama sees the traits of these heroes within his own children, and within all of America's children"--Book jacket.